2012
DOI: 10.1073/pnas.1207213109
|View full text |Cite
|
Sign up to set email alerts
|

The DNA virus Invertebrate iridescent virus 6 is a target of the Drosophila RNAi machinery

Abstract: RNA viruses in insects are targets of an RNA interference (RNAi)-based antiviral immune response, in which viral replication intermediates or viral dsRNA genomes are processed by Dicer-2 (Dcr-2) into viral small interfering RNAs (vsiRNAs). Whether dsDNA virus infections are controlled by the RNAi pathway remains to be determined. Here, we analyzed the role of RNAi in DNA virus infection using Drosophila melanogaster infected with Invertebrate iridescent virus 6 (IIV-6) as a model. We show that Dcr-2 and Argona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
160
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(172 citation statements)
references
References 78 publications
11
160
0
1
Order By: Relevance
“…Recently, it was revealed that hosts can use virus-derived siRNA or cellular miRNA to restrict viral propagation (18,(21)(22)(23)(24). In turn, a number of viruses, in particular DNA viruses, seem to have evolved mechanisms to express their own miRNAs and employ miRNA-mediated regulations to counter host antiviral responses (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was revealed that hosts can use virus-derived siRNA or cellular miRNA to restrict viral propagation (18,(21)(22)(23)(24). In turn, a number of viruses, in particular DNA viruses, seem to have evolved mechanisms to express their own miRNAs and employ miRNA-mediated regulations to counter host antiviral responses (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…siRNA is subsequently loaded into a RNA-induced silencing complex (RISC) that cleaves the targeted RNA (91). While RNAi is typically thought of as a mechanism directed against RNA viruses, several recent reports (92)(93)(94) demonstrated the presence of siRNAs directed against insect dsDNA viruses (invertebrate iridovirus 6 [IIV-6] and the baculovirus Helicoverpa armigera single nucleopolyhedrovirus [HaSNPV]). In both cases, Dicer-2 (the primary RNase associated with the insect RNAi response) was associated with production of siRNAs, and in both cases, hotspots of RNAi were identified in the viral genome.…”
Section: Discussionmentioning
confidence: 99%
“…IIV-6 and FHV are not natural Drosophila viruses. Nevertheless, both are able to replicate in D. melanogaster under experimental conditions (49)(50)(51). IIV-6 is commonly used as a DNA virus model, and we thought that vpiRNAs could originate from a DNA source, as is the case for endogenous piRNAs.…”
Section: Isogenization and Characterization Of Pirna Mutant Flies On mentioning
confidence: 98%